Pay dirt road - Allen, Samantha Jayne (Minotaur Books, 2022)
"Friday Night Lights meets Mare of Easttown in this small-town mystery about an unlikely private investigator searching for a missing waitress. Pay Dirt Road is the mesmerizing debut from the 2019 Tony Hillerman Prize recipient Samantha Jayne Allen. Annie McIntyre has a love/hate relationship with Garnett, Texas. Recently graduated from college and home waitressing, lacking not in ambition but certainly in direction, Annie is lured into the family business-a private investigation firm-by her supposed-to-be-retired grandfather, Leroy, despite the rest of the clan's misgivings. When a waitress at the café goes missing, Annie and Leroy begin an investigation that leads them down rural routes and haunted byways, to noxious-smelling oil fields and to the glowing neon of local honky-tonks. As Annie works to uncover the truth she finds herself identifying with the victim in increasing, unsettling ways, and realizes she must confront her own past-failed romances, a disturbing experience she'd rather forget, and the trick mirror of nostalgia itself-if she wants to survive this homecoming"--